2022
DOI: 10.3390/ijerph19074078
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Aboriginal Models of Selfhood: The National Empowerment Project’s Cultural, Social, and Emotional Wellbeing Program in Western Australia

Abstract: Culturally safe and responsive interventions that acknowledge Aboriginal models of selfhood are needed. Such interventions empower Aboriginal peoples and communities by increasing self-determination over individual and community social and emotional wellbeing (SEWB). In response to this need, the National Empowerment Project developed the Cultural, Social, and Emotional Wellbeing Program (CSEWB). The CSEWB aims to strengthen SEWB and cultural identity and subsequently reduce psychological distress in Aborigina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…(3) Explore how small group and one-on-one opportunities for experiential learning could be adapted to reinforce and consolidate the content into weekly workbook exercises through peer group discussion or direct contact between instructors and participants investigation of mediation or moderation efects based on demographic characteristics, mental health status, relationship characteristics, and program adherence [50]. For example, cultural background was found to infuence the efectiveness of some mental health interventions [78,92]. Future research might consider how to select participants for trials of targeted preventive interventions [83] and whether diferent participants respond to diferent forms of interventions based on factors such as symptom severity [104].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Explore how small group and one-on-one opportunities for experiential learning could be adapted to reinforce and consolidate the content into weekly workbook exercises through peer group discussion or direct contact between instructors and participants investigation of mediation or moderation efects based on demographic characteristics, mental health status, relationship characteristics, and program adherence [50]. For example, cultural background was found to infuence the efectiveness of some mental health interventions [78,92]. Future research might consider how to select participants for trials of targeted preventive interventions [83] and whether diferent participants respond to diferent forms of interventions based on factors such as symptom severity [104].…”
Section: Discussionmentioning
confidence: 99%
“…Tese fndings highlight the importance of increasing emphasis on family and community protective factors in adolescent social-emotional development and depression prevention programs [66,82,97]. Additional advantages reported for lighttouch interventions were being evidence-based (e.g., CBT [67,96]) and able to be adapted for the target population [64,68,70,78,98,102]. For example, a men's health promotion program Sons of the West attributed their high participation rates to the broad-ranging, gendersensitised format [75].…”
Section: Strengths and Limitations Light-touch Interventionsmentioning
confidence: 99%
“…Independent evaluations and qualitative evaluations of this intervention have consistently found that participants report improved social and emotional wellbeing, strengthened resilience, and decreased psychological distress. 8 9 10 …”
Section: Cultural Reclamationmentioning
confidence: 99%
“…The benefits of relational self-care include the strengthening of sustainable health practices, inter-generational healing, health and wellbeing literacy, and increased self-determination over individual and collective health. 10 Relational self-care also supports Indigenous human rights by advancing decolonisation and supporting communities in their search for truth and empowerment, while nurturing the knowledge of collective resilience and a desire for an equitable future.…”
Section: Cultural Reclamationmentioning
confidence: 99%
“…Climate distress appears to be more common in young people, Indigenous people, those who have directly experienced climate impacts, and women, although the findings on women have been variable between cohorts living in the United States and those living elsewhere (Clayton, 2020;Heeren et al, 2022;Middleton et al, 2020). It is unsurprising that Indigenous Peoples around the world are particularly at risk for climate distress, given the emphasis that many Indigenous cultures place on connection to and care for country, and, for many Aboriginal and Torres Strait Islander communities, the adverse impact on social and emotional wellbeing of the historical and ongoing impacts of colonisation, Stolen Generations, and genocide (Dudgeon et al, 2022;Lansbury Hall & Crosby, 2022). Similarly, it makes sense that young people, who are likely to live to see more extreme disruptions to the climate system, appear to experience climate distress in larger numbers than older cohorts (Heeren et al, 2022).…”
Section: /15mentioning
confidence: 99%